2020
DOI: 10.1111/cogs.12905
|View full text |Cite
|
Sign up to set email alerts
|

What Eye Movements Reveal About Later Comprehension of Long Connected Texts

Abstract: We know that reading involves coordination between textual characteristics and visual attention, but research linking eye movements during reading and comprehension assessed after reading is surprisingly limited, especially for reading long connected texts. We tested two competing possibilities: (a) the weak association hypothesis: Links between eye movements and comprehension are weak and short-lived, versus (b) the strong association hypothesis: The two are robustly linked, even after a delay. Using a predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 77 publications
(139 reference statements)
3
14
0
Order By: Relevance
“…Moreover, they demonstrated that decoupling measured in instances of mind-wandering resulted in worse text comprehension. Moreover, Southwell and colleagues (2020) showed that comprehension scores can be successfully predicted from reading times and classical eye movement measures. However, it remains unclear why the same measures yielded null effects in other studies ( Wallot et al, 2015 ) or related reading speed components during self-paced reading ( LeVasseur et al, 2006 , 2008 ; Wallot et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they demonstrated that decoupling measured in instances of mind-wandering resulted in worse text comprehension. Moreover, Southwell and colleagues (2020) showed that comprehension scores can be successfully predicted from reading times and classical eye movement measures. However, it remains unclear why the same measures yielded null effects in other studies ( Wallot et al, 2015 ) or related reading speed components during self-paced reading ( LeVasseur et al, 2006 , 2008 ; Wallot et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Southwell, Gregg, Bixler, and D'Mello (2020) predicted reading comprehension scores in three datasets using seven global eye-movement measures (number of fixations, average fixation duration, mean saccade length, proportion of regressions, proportion of horizontal saccade, fixation dispersion, and reading time). In all three datasets, participants were given long passages of text to read silently, followed by multiple-choice questions.…”
Section: Predicting Comprehension Accuracy From Eye-movement Behaviourmentioning
confidence: 99%
“…In the last decades, researchers have investigated eye movements as a potential measure of language and reading ability. Several studies have suggested that features of eye-movement behavior during reading such as fixation durations, saccade length, and regression rates could be used to estimate second language proficiency (Berzak et al, 2018;Reich et al, 2022), classify readers at risk of dyslexia (Benfatto et al, 2016;Rello & Ballesteros, 2015), as well as estimate performance on reading comprehension assessments (Copeland et al, 2014(Copeland et al, , 2016Copeland & Gedeon, 2013;D'Mello et al, 2020;Inhoff et al, 2018;Martínez-Gómez & Aizawa, 2014;Mézière et al, 2022;Reich et al, 2022;Southwell et al, 2020).…”
mentioning
confidence: 99%
“…Studies on the relationship between eye movements and reading comprehension accuracy have shown that eye-movement behavior can successfully predict performance on commonly-used reading comprehension tasks, including cloze tasks (Copeland et al, 2014;Mézière et al, 2022), multiple-choice comprehension questions (D'Mello et al, 2020;Inhoff et al, 2018;Southwell et al, 2020), and open-ended questions (Mézière et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation